Current quality of life questionnaires are not relevant for assessing QOL issues in multiple myeloma patients in the era of modern therapies: results from a survey with myeloma patients and myeloma healthcare professionals - Lecat, Catherine S. Y.; Bristogiannis, Sotirios; Mehta, Dipal; Lwin, Yadanar; Land, Joanne; McCourt, Orla; Dowling, Emma; Correia, Nuno; Rabin, Neil K.; Xu, Ke; Sive, Jonathan; Papanikolaou, Xenofon; et al. (Frontiers in Oncology, 2025)
As multiple myeloma (MM) patients live longer, maintaining quality of life (QOL) has become an important treatment goal. However, the commonly used general quality of life questionnaires (QOLQs) were developed over 20 years ago. In this survey, 224 MM patients and 48 healthcare professionals (HCPs) were asked to grade the relevance and importance of QOL items from 9 validated, frequently used MM QOLQs. The results from this survey highlighted significant discrepancy between MM patients’ and HCPs’ perception of important and relevant QOL issues. Whilst MM HCPs found all QOL items relevant, the patients reported a proportion of these items being relevant. These were mainly related to physical functioning, social/family wellbeing, pain and fatigue. This real-world survey stressed the need for the development of an updated QOLQ that is relevant to patients and current MM therapies.